ACG Clinical Guideline: Ulcerative Colitis in Adults. (March 2019) - Rubin, David T.; Ananthakrishnan, Ashwin N.; Siegel, Corey A.; Sauer, Bryan G.; Long, Millie D.
Abstract : Ulcerative colitis (UC) is an idiopathic inflammatory disorder. These guidelines indicate the preferred approach to the management of adults with UC and represent the official practice recommendations of the American College of Gastroenterology. The scientific evidence for these guidelines was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) process. In instances where the evidence was not appropriate for GRADE, but there was consensus of significant clinical merit, "key concept" statements were developed using expert consensus. These guidelines are meant to be broadly applicable and should be viewed as the preferred, but not only, approach to clinical scenarios.